(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
In this article studying the current state of development of students’ legal competence, implementing plans to eliminate shortcomings, and seeking measures for its development determine the goal of achieving the systematic implementation of tasks from scientific-theoretical, legal, and practical perspectives.